An Efficient and Mild Synthesis of Tetrahydro-4H-indol-4-one Derivatives via a Domino Reaction in Water - Zhang, Furen; Li, Chunmei; Qi, Chenze (Synthesis, 2013)
An efficient domino approach for the synthesis of tetrahydro-4H-indol-4-one derivatives has been established. The use of catalytic amount of l-proline in water at 60 °C makes it quite simple, more convenient, and environmentally benign.
Keywords: tetrahydro-4H-indol-4-one; amines; cyclization; domino reaction; catalysis